Index of conditionally-pathogenic microflora: forecasting the risk of dysbiosis development - A. A. Gruzevskiy (Kazimierz Wielki University, 2018)
Bacterial vaginosis is one of the most common types of infectious pathology of the reproductive organs of women mainly in reproductive age. The frequency of bacterial vaginosis over the past decade has doubled, ranging from 26% to 40-45%. Until now, the leading role in the emergence of bacterial vaginosis of obligate anaerobic bacteria has been proved, which is why it is regarded as a polymicrobial vaginal syndrome and is characterized not only by vaginal discharge, but also by damage to the cervix, the uterus, its appendages, childbirth. The etiological structure of pathogens of infectious processes in the last decade has changed significantly, which is due to the constant evolution of bacteria and the involvement of conventionally pathogenic microorganisms into pathological processes. The aim of the study is to identify the most informative indicators that objectively reflect the condition of the pathological process and develop a system for predicting the risk of occurrence and severity of dysbiosis behind these indicators. Materials and methods of research Studies were conducted in 298 women aged 16 to 64 years. 53 of whom were diagnosed with normocenosis, and 245 had dysbiosis. Statistical processing of data was carried out using variational and correlation analysis methods using the Statistica v. Application software package. 10 (StatSoft, Inc.). The results of the study and their discussion At the first stage of the analysis, the index of conditionally pathogenic microflora was considered as a resultant trait. To identify factors that are more associated with the risk of developing dysbiosis with IPM, a selection of significant traits was performed using a genetic selection algorithm. At the second stage of the analysis, the prediction of the severity of dysbiosis with IСPM was considered. Conclusions. The nine factor attributes obtained with the help of mathematical analysis allowed us to predict the severity of vaginal dysbiosis with high accuracy and to calculate the IPM indices. In addition, the phase of the development of the immune system reaction is shown in the development of vaginal dysbiosis - from the control state during normocoenosis to the development of immunorequency in dysbiosis of grade 1 and expressed combined immunodeficiency in the presence of specific humoral response to bacterial antigens in dysbiosis of the 2nd degree.